(untitled) (Mūzikas akadēmijas raksti, 2024)
The research object of this paper is form-building of Pierre Boulez's Tombeau for orchestra and soprano (1959–1962). The piece is inspected from two different angles: first, the focus is on its aural appearance (applying some of the analytical tools of aural sonology); thereafter the composition technique is under scrutiny.